Avanços na criopreservação do sêmen ovino I: diluidores e crioprotetores - Bittencourt, Rodrigo Freitas; Oba, Eunice [UNESP]; Ribeiro Filho, Antônio De Lisboa; Chalhoub, Marcos; Azevedo, Hymerson Costa; Bicudo, Sony Dimas [UNESP] (Universidade Federal de Goiás, 2013)
The effectiveness of using frozen sheep semen in artificial insemination programs requires the development of extenders and freezing protocols that will increase pregnancy rate of inseminated females. This work aimed to survey the main extenders, additives and external and internal cryoprotectants that have been employed to improve the maintenance levels of sperm parameters after the freezing-thawing process. Better rates of post-thawing sheep sperm viability may be obtained with changes in the freezing extender composition, whether by the adjustment of its components or by introducing additives that inhibit the occurrence of sperm changes during the cryopreservation process. Thus, the possible changes proposed must take into consideration the intrinsic characteristics of ram semen and the individual variability among animals. It is important to emphasize that the sperm cryopreservation effectiveness requires that all process steps are conducted in an integrated manner, to maximize the fertility rate of frozen ram semen.

A eficácia da utilização de sêmen ovino congelado em programas de inseminação artificial necessita do desenvolvimento de diluidores e protocolos de congelação que melhorem a taxa de gestação das fêmeas inseminadas. Este trabalho tem como objetivo fazer um levantamento dos principais diluidores, aditivos, crioprotetores penetrantes e não penetrantes que veem sendo empregados, visando incrementar os níveis de manutenção dos parâmetros espermáticos, após o processo de congelação-descongelação. Pode-se considerar que índices superiores de viabilidade do sêmen ovino pós-descongelação podem ser obtidos com alterações na composição do meio de congelação, seja com ajustes dos seus componentes, seja com a introdução de aditivos que inibam a ocorrência de alterações espermáticas durante o processo de criopreservação. Para tanto, as possíveis modificações propostas devem contemplar as características intrínsecas do sêmen da espécie e a variabilidade individual entre animais. É importante ressaltar que um adequado processo de criopreservação do sêmen necessita que todas as etapas sejam conduzidas de forma integrada, para que, dessa forma, sejam maximizados os índices de fertilidade do sêmen ovino congelado.
Advances in cryopreservation of ram semen I: extenders and cryoprotectans
Keywords: aditivos; crioagentes; Ovis aries; sêmen congelado; additives; cryoagents; frozen semen; Ovis aries